The value of things : prehistoric to contemporary commodities in the Maya region - Guderjan, Thomas H.; Mathews, Jennifer P., 1969- (The University of Arizona Press, 2017)
"This book explores how the Mayans gave value to commodities through the lens of anthropology and archaeology"--Provided by publisher.